Spray deposit variability in New Zealand winegrape canopies and implications for agrichemical application practices - Manktelow, D.W.L.; Praat, J-P. (New Zealand Plant Protection, 2000)
Introduction of new grape sprayers and vineyard planting systems in New Zealand has led to uncertainty over agrichemical application rate requirements in different canopies A 1998 survey of spray application practices on 15 Hawkes Bay vineyards found up to a sixfold difference between vineyards in the rates of sulphur fungicides applied to fully developed canopies Followup work in 199900 found that twofold withincanopy spray deposit variations were common Earlier work indicated that deposits on upper surfaces of leaves can be up to three times greater than on lower surfaces Methods for reducing deposit variations and for more precise definition of agrichemical application rate requirements are discussed